Physiological demands of fencing: A narrative review - Oates, L. W.; Price, M. J.; Bottoms, L M. (Journal of Elite Sport Performance, 2023)
Background and Aim Fencers compete over long competition days (9-11 hours) wearing full body protective clothing whilst performing high-intensity explosive movements interspersed with low intensity preparatory or recovery movements. Therfore the aim of this review is to provide contemporary perspectives of the literature discussing the physiological and thermoregulatory demands of fencing to inform training, competition, and recovery practices.